2022
DOI: 10.3390/biomedicines10102374
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and High Blood Pressure: Mechanistic Insight on the Role of the Kidney

Abstract: The metabolic effects of insulin predominate in skeletal muscle, fat, and liver where the hormone binds to its receptor, thereby priming a series of cell-specific and biochemically diverse intracellular mechanisms. In the presence of a good secretory reserve in the pancreatic islets, a decrease in insulin sensitivity in the metabolic target tissues leads to compensatory hyperinsulinemia. A large body of evidence obtained in clinical and experimental studies indicates that insulin resistance and the related hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 118 publications
0
12
0
Order By: Relevance
“…Therefore, research is needed to be considered as a significant indicator for predicting hypertension and MetS, which should help reduce the risk of hypertension and MetS in police personnel promptly. Insulin resistance has been found to play a significant causal role in developing hypertension ( Brosolo et al, 2022 ) and cardiovascular diseases ( Di Pino & DeFronzo, 2019 ). Endothelial dysfunction, vascular resistance, the activity of the sympathetic nervous system, renal sodium and fluid retention, and the subsequent renin-angiotensin-aldosterone system may play a crucial part in the etiology of hypertension when insulin resistance is present ( Brosolo et al, 2022 ; Janus et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, research is needed to be considered as a significant indicator for predicting hypertension and MetS, which should help reduce the risk of hypertension and MetS in police personnel promptly. Insulin resistance has been found to play a significant causal role in developing hypertension ( Brosolo et al, 2022 ) and cardiovascular diseases ( Di Pino & DeFronzo, 2019 ). Endothelial dysfunction, vascular resistance, the activity of the sympathetic nervous system, renal sodium and fluid retention, and the subsequent renin-angiotensin-aldosterone system may play a crucial part in the etiology of hypertension when insulin resistance is present ( Brosolo et al, 2022 ; Janus et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance has been found to play a significant causal role in developing hypertension ( Brosolo et al, 2022 ) and cardiovascular diseases ( Di Pino & DeFronzo, 2019 ). Endothelial dysfunction, vascular resistance, the activity of the sympathetic nervous system, renal sodium and fluid retention, and the subsequent renin-angiotensin-aldosterone system may play a crucial part in the etiology of hypertension when insulin resistance is present ( Brosolo et al, 2022 ; Janus et al, 2016 ). The previous report indicated the correlation between the LAP, TG/HDL-c, TyG index and VAI with a HOMA-IR, which reflex the predictive ability of insulin resistance by these indices ( Huang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, under IR/Hyperins conditions, the excessive stimulation of the MAPK cascade, which has vasoconstrictive (ↄ ET-1) and growth-promoting effects at various cellular levels, ends up determining part of the deleterious effects at the cardiovascular level. At this point there is also solid evidence to support the fact that Hyperins may also be a determinant of arterial hypertension, in fact it has been demonstrated that insulin causes retention of sodium and water in the kidney, and that both endogenous and exogenous Hyperins were found related to increases in blood pressure ( 28 ) ( Figure 1 ). In fact, insulin receptors have been detected in the renal tubules, and their stimulation by insulin has been shown to produce increased sodium reabsorption.…”
Section: Effects Of Insulin Resistance/hyperinsulinemia On Cardiovasc...mentioning
confidence: 92%
“…Causes of secondary hypertension were ruled out according to current guidelines (35) after clinical, biochemical (urine analysis, creatinine clearance, plasma aldosterone, renin, and cortisol, free urinary cortisol and epinephrine, norepinephrine, and dopamine) and instrumental tests (ECG, echocardiography, renal ultrasound, and renal angio-CT and adrenal CT scan when indicated) (36). Diabetes was excluded by measurement of fasting blood glucose and glycated hemoglobin, and by a standard oral glucose tolerance test (37). Smokers were defined if they smoked for more than 5 years and did not quit more than 1 year before examination.…”
Section: Patientsmentioning
confidence: 99%